Indigeneity and the Disruption of Anglo-Australian Nationalism in Australian Football - Judd, Barry; Hallinan, Christopher (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Situated in the overall context of the ideals of the nation, this article outlines the formation of Anglo-Australian nationhood and its strong connection to sport, the historical treatment of Indigenous Australians as "others", and the inherent racism within the nation and within sports systems. The vocal antagonism directed at a leading player who was also named Australian of Year is described and analyzed within the framework of conditional contemporary change, protests by the general public, and the emerging resistance by leading Indigenous Australians to Anglo-idealized nationhood.
Keywords: football; nationalism; racism; indigenous